Calcite raft geochemistry as a hydrological proxy for Holocene aquifer conditions in Hoyo Negro and Ich Balam (Sac Actun Cave System), Quintana Roo, Mexico. (1st November 2017) - Kovacs, Shawn E.; Reinhardt, Eduard G.; Chatters, James C.; Rissolo, Dominique; Schwarcz, Henry P.; Collins, Shawn V.; Kim, Sang-Tae; Nava Blank, Alberto; Luna Erreguerena, Pilar
Abstract: Two cores from calcite rafts deposits located in Cenote Ich Balam and Hoyo Negro were dated and analyzed for 87 Sr/ 86 Sr, δ 18 O, δ 13 C, Sr/Ca and Cl/Ca. The geochemical records show changing aquifer salinity spanning the last ∼ 8.5 cal kyrs BP and interrelationships with Holocene climate trends (wet and dry periods). During the wet mid-Holocene, the salinity of the meteoric Water Mass (WM; at 7.8–8.3 cal kyrs BP) was relatively high at 1.5–2.7 ppt and then became less saline (1.0–1.5 ppt) during the last ∼ 7000 yrs as climate became progressively drier. High salinity of the meteoric WM during the wet mid-Holocene is attributed to increased turbulent mixing between the meteoric and underlying marine WM. Increased precipitation, in terms of amount, frequency, and intensity (e.g. hurricanes) causes higher flow of meteoric water towards the coast and mixing at the halocline, a phenomenon recorded with recent instrumental monitoring of the aquifer. Conversely, during dry periods reduced precipitation and flow in the meteoric WM would result in lower salinity. Karst properties and Holocene sea-level rise also seem to have an effect on the aquifer. When the regionally extensive network of shallow cave passages (∼ 10–12 m water depth) are flooded at ∼ 8000 cal yrs BP, there is a rapid shift in salinity. This study demonstrates that calcite raft deposits can be used as paleo-environmental recorders documenting the effects of sea level and climate change on aquifer condition. Highlights: Geochemistry of calcite rafts reconstructs past aquifer condition. Aquifer in Hoyo Negro was more saline during the wet mid-Holocene (7.8–8.3 cal kyrs BP). Aquifer salinity responds to mixing between the meteoric and marine water masses. Calcite rafts are used for the first time as a paleohydrological proxy. Implications for early Paleoamerican subsistence in the Yucatan Peninsula.